Air Temperature and Humidity Monitoring System for Oyster Mushroom Cultivation - Ardani, Hasby Arif; Maulindar, Joni; Indah, Ratna Puspita (Politeknik Negeri Lhokseumawe, 2025)
Oyster mushroom cultivation demands the stability of the microenvironment, especially in the aspects of temperature and humidity in the barn space. Manual monitoring methods that are still commonly used are often less responsive and inefficient in capturing real-time changes in conditions. To answer these problems, this research designs and builds an Internet of Things (IoT)-based monitoring system integrated with the Ubidots platform as a control center and data visualization. This system is able to read and send precise temperature and humidity data using the Hypertext Transfer Protocol (HTTP) protocol. This system uses the DHT22 sensor which is more accurate than previous studies that generally use the DHT11 sensor. The test results show that the system works responsively, stably, and accurately in presenting real-time environmental data, with a temperature reading error rate of about ±0.5°C and ±5% humidity. The implementation of the system at the oyster mushroom cultivation site in Jonggrangan Village, Klaten Utara, proved its effectiveness in helping farmers monitor and maintain mushroom growth conditions remotely in an efficient and sustainable manner.Oyster mushroom cultivation demands the stability of the microenvironment, especially in the aspects of temperature and humidity in the barn space. Manual monitoring methods that are still commonly used are often less responsive and inefficient in capturing real-time changes in conditions. To answer these problems, this research designs and builds an Internet of Things (IoT)-based monitoring system integrated with the Ubidots platform as a control center and data visualization. This system is able to read and send precise temperature and humidity data using the Hypertext Transfer Protocol (HTTP) protocol. This system uses the DHT22 sensor which is more accurate than previous studies that generally use the DHT11 sensor. The test results show that the system works responsively, stably, and accurately in presenting real-time environmental data, with a temperature reading error rate of about ±0.5°C and ±5% humidity. The implementation of the system at the oyster mushroom cultivation site in Jonggrangan Village, Klaten Utara, proved its effectiveness in helping farmers monitor and maintain mushroom growth conditions remotely in an efficient and sustainable manner.